Spatial Analysis of HIV Case Distribution and Key Population Distribution in Bandung City - Alnidi Safarach Bratanegara; Aldi Maulana Yusuf; Fiqhi Adha Arlisadi (Department of Geography Education, Faculty of Social Sciences, Universitas Negeri Medan, 2022)
HIV is a disease that can attack a person's immune system, and there is no effective drug to eliminate HIV disease. Indonesia is one of the countries with the fifteenth largest population affected by HIV disease in the world. The city of Bandung is the area that has the most HIV cases in the province of Java; based on data from the Bandung City Health Office, there were 4,620 people infected with HIV in 2018. The purpose of this study was to analyze the relationship between the distribution of HIV cases and the distribution of key populations in the city of Bandung. The research method used is a quantitative description method by collecting various secondary data from the health department so that it is processed using a Geographic Information System. The spatial analysis used is the Spatial Autocorrelation Report, which will describe based on data on HIV cases and key populations. The results of the study illustrate that HIV cases have a random distribution pattern and have no correlation between locations and HIV cases. Meanwhile, the distribution pattern of the key population has a random distribution pattern or does not correlate with the location and the key population, so there is a tendency for a relationship between HIV cases and the number of key populations.Keywords: HIV, Key Population, Geography Information System, Bandung